(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
Traditional health services are alternative therapies to solve public health problems. The development of traditional health services, in accordance with the enthusiasm of people in traditional medicine, that the government has the authority to improve and control traditional medical services as a manifestation of protection for the community. Through law No.36 of 2009 concerning health. Then supported by the Regulation of the Minister of Health of the Republic of Indonesia No10761Menkes / SKIVII1 / 2003 concerning the Implementation of Traditional Medicine where the government formed a Center for the Development and Application of Traditional Medicine (SP3T) which is required to carry out an examination of every traditional medical service.